2023
DOI: 10.1021/acsami.3c06188
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots Derived from Herbal Medicine as Therapeutic Nanoagents for Rheumatoid Arthritis with Ultrahigh Lubrication and Anti-inflammation

Abstract: As a typical chronic inflammatory joint disease with swelling and pain syndromes, rheumatoid arthritis (RA) is closely related to articular lubrication deficiency and excessive proinflammatory cytokines in its progression and pathogenesis. Herein, inspired by the dual effects of joint lubrication improvement and anti-inflammation to treat RA, two novel potential therapeutic nanoagents have been developed rationally by employing herbal medicine-derived carbon quantum dots (CQDs), i.e., safflower (Carthamus tinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It was found that CQDs obtained from herbal medicines greatly reduced swelling signs and impeded the production of associated inflammation cytokines (IL-1, IL-6, and TNF-α), demonstrating exceptional anti-inflammation efficacy. 561 Liu et al suggested HIF-1 siRNA-carried calcium phosphate NPs enclosed in high-density lipoprotein-modified with apolipoprotein E3 (HIF-CaP-rHDL) as a treatment for RA in order to suppress the levels of HIF-1, NF-κB, and MAPK. By blocking these pro-inflammatory signaling pathways and attenuating cytokines including TNF-α, IL-1β, and IL-6, HIF-CaP-rHDL showed promise as a targeted remedy for RA.…”
Section: Nanotechnology In Non-infectious Inflammatory Diseasesmentioning
confidence: 99%
“…It was found that CQDs obtained from herbal medicines greatly reduced swelling signs and impeded the production of associated inflammation cytokines (IL-1, IL-6, and TNF-α), demonstrating exceptional anti-inflammation efficacy. 561 Liu et al suggested HIF-1 siRNA-carried calcium phosphate NPs enclosed in high-density lipoprotein-modified with apolipoprotein E3 (HIF-CaP-rHDL) as a treatment for RA in order to suppress the levels of HIF-1, NF-κB, and MAPK. By blocking these pro-inflammatory signaling pathways and attenuating cytokines including TNF-α, IL-1β, and IL-6, HIF-CaP-rHDL showed promise as a targeted remedy for RA.…”
Section: Nanotechnology In Non-infectious Inflammatory Diseasesmentioning
confidence: 99%
“…New nanoagents for rheumatoid arthritis treatment could be developed by combining the lubricating and anti-inflammatory bioefficacy of CQDs generated from herbal medicine (Fig. 14 ) 147 .…”
Section: Nanotheranostics For Multiple Disease Of Herbal Bioactivesmentioning
confidence: 99%
“…Medicinal plants for RA treatment have gained attention due to their potential therapeutic benefits and fewer side effects compared to conventional drugs [ 8 ]. Various plants with anti-inflammatory, analgesic, and immunomodulatory properties have been traditionally employed to alleviate RA symptoms.…”
Section: Introductionmentioning
confidence: 99%